TINDAK UJAR ILOKUSI DALAM NOVEL THE GUARDIAN KARYA NICHOLAS SPARKS - KORDAK, ALFRITS; JANSEN, FRIEDA TH.; MANUS, JEANE A. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2019)
ABSTRACTÂ Â Â Â Â Â Â Â Â Â Â  Language is one of the most important and characteristic forms of human behavior. In communication, people not only utter sentences but also transfer into behavior and this is called speech act. According to Searle, illocutionary act is divied into five categories, which are :assertives, directives, commisives, expressives, and declaratives.The purpose of this research is to identify and analyze the function of illocutionary acts in the novel â€œThe Guardianâ€ by Nicholas Sparks. The collected data have been identified to the utterances hich contain illocutionary acts that are used by the characters in the novel and descriptively based on the theory of Searle.In this research finding, it shows that there are five kinds of illocutionary acts in the novel. Those are assertives, directives, commisives, expressives, and declaratives. The function of illocutionary act in the novel are reporting, asserting, complaining, requesting, advising, begging, offering, thanking, and praising.The outcome of this study is to give contribution of the language development in linguistic studies especially in analyzing illocutionary acts through pragmatic analysis and to be expected to help the students of English Departement in understanding the illocutionary act so that they can identify and analyze the illocutionary act in daily life.Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Keywords : Illocutionary Act, Novel The Guardian